Chemical constituents of some essential oils bearing plants growing wild in Vietnam - Nguyen Phuong, Hanh; Nguyen Thi Hien,; Nguyen , Quoc Binh; Dinh, Thi Thu Thuy (Academia Journal of Biology, 2023)
The essential oils of three plants were isolated by hydrodistillation and their constituents were analyzed by gas chromatography-mass spectrometry/flame ionization detection (GC/MS-FID) method. 29 compounds representing 99.00% of the total oil of inflorescences of Zingiber pellitum were identified, consisting mainly of α-pinene (5.34%), β-caryophyllene (39.13%) and α-humulene (36.69%). For Basilicum polystachyon, 41 and 37 components were identified in the leaf and flower oils, accounting for 91.32% and 92.44% of the total oils, respectively. Germacrene D (16.33% and 16.32%), germacrene B (14.95% and 16.23%), α-cubebene (13.38% and 19,04%), α-copaene (5.81% and 5.77%), δ-cadinene (4.78% and 4.18%), β-cis-elemene (4.34% and 4.66%), and γ-elemene (4.31% and 4.72%) were the major constituents in both oils. For the leaves of Litsea bavienes, 40 components were identified, representing 91.73% of the total oil contents, in which hepten-3-one (70.46%) was the most abundant compound in this oil. The chemical constituents of essential oils from Z. pellitum (inflorescences), B. polystachyon (leaves and flowers) and L. baviensis (leaves) were being reported for the first time.